Odpowiedź:
Proszę bardzo! :)
C)
[tex]\frac{3x+2}{3x-2}=4-x[/tex]
ZAŁOŻENIA:
1)
[tex]3x-2\neq 0\\3x\neq 2\ \ \ /:3\\\\x\neq \frac{2}{3}[/tex]
D=R\{[tex]\frac{2}{3}[/tex]}
[tex]\frac{3x+2}{3x-2}=4-x \ \ \ /*(3x-2)\\\\3x+2=(4-x)(3x-2)\\3x+2=12x-8-3x^2+2x\\3x^2+3x-12x-2x+2+8=0\\3x^2-11x+10=0\\[/tex]
Δ[tex]=b^2-4ac\\[/tex]
[tex]delta=(-11)^2-4*3*10=121-120=1 \ \ \ /\sqrt{}\\ \sqrt{delta}=1[/tex]
[tex]x_{1}=\frac{-b-\sqrt{delta} }{2a}=\frac{11-1}{6}=\frac{10}{6}=\frac{5}{3}\\\\ x_{2}=\frac{-b+\sqrt{delta} }{2a}=\frac{11+1}{6}=\frac{12}{6}=2[/tex]
x∈{[tex]2;\frac{5}{3}[/tex]}
F)
[tex]\frac{x+3}{3-x}=\frac{x}{x+1}[/tex]
ZAŁOŻENIA:
1)
[tex]3-x\neq 0\\3\neq x[/tex]
2)
[tex]x+1\neq 0\\x\neq -1[/tex]
D=R\{[tex]-1;3[/tex]}
[tex]\frac{x+3}{3-x}=\frac{x}{x+1}[/tex]
Mnożymy na krzyż!
[tex](x+3)(x+1)=x(3-x)\\x^2+x+3x+3=3x-x^2\\x^2+x^2+3x+x-3x+3=0\\2x^2+x+3=0\\[/tex]
Δ=[tex]b^2-4ac[/tex]
[tex]delta=(1)^2-4*2*3=1-24=-23[/tex]
Δ<0 (brak rozwiązań)
Szczegółowe wyjaśnienie: